Sistem Informasi Perpustakaan Berbasis Web Application - Yudie Irawan (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2016)
Digital library system contributes the development of digital resource digital resource that can be accessed via the Internet. Librarymanagement system contributed to the development of automation membership data processing, circulation and cataloging. In this thesisis to develop a new concept of digital library systems and library management system by integrating these two systems architecture. Integration architecture implemented by inserting component library management system into the digital library system architecture. Web application technology required for these components in order to be integrated with the digital library system components. The newsystem has the advantage of this development application utilization of borrowing, membership and kataloging to a sharable over theinternet, so applications that can be used together. Information can be delivered between the library catalog, without leaving the digitallibrary function in the utilization of shared digital resources derived from uploading by each librarian.